2023
DOI: 10.1177/19458924231207123
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Outcome Measures in Individuals With Hereditary Hemorrhagic Telangiectasia: A Scoping Review

Anna J. Gong,
Tushar Garg,
Adham Khalil
et al.

Abstract: Background Studies evaluating health-related quality of life (HRQOL) in patients with hereditary hemorrhagic telangiectasia (HHT) have expanded rapidly in the past decade. These studies have evaluated QOL aspects ranging from the general QOL for patients living with HHT to intervention-specific outcomes. However, few tools have been fully validated across the spectrum of disease manifestations and interventions in HHT. Objective In this scoping review, we aim to map the literature on HHT-QOL metrics, identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…In another study performed by the same team, Gong et al performed a scoping review of studies on health-related quality of life in patients with hereditary HHT to identify existing metrics, gaps, and guide future research. 7 The heterogeneity in outcomes measures across studies that they found highlights the need for further development of HHT-specific patient-reported outcomes instruments.…”
mentioning
confidence: 99%
“…In another study performed by the same team, Gong et al performed a scoping review of studies on health-related quality of life in patients with hereditary HHT to identify existing metrics, gaps, and guide future research. 7 The heterogeneity in outcomes measures across studies that they found highlights the need for further development of HHT-specific patient-reported outcomes instruments.…”
mentioning
confidence: 99%